2019
DOI: 10.2478/ace-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Hybrid FRP Bars and Nano-Hybrid FRP Bars

Abstract: The paper describes the recent developments of Hybrid Fibre-Reinforced Polymer (HFRP) and nano-Hybrid Fibre-Reinforced Polymer (nHFRP) bars. Hybridization of less expensive basalt fibres with carbon fibres leads to more sustainable alternative to Basalt-FRP (BFRP) bars and more economically-efficient alternative to Carbon-FRP (CFRP) bars. The New-Developed HFRP bars were subjected to tensile axial loading to investigate its structural behaviour. The effect of hybridization on tensile properties of HFRP bars wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The results for different fibers arrangement and different volume fractions of fibers are described in Table 1. The comparison between analytical considerations and numerical simulations of FRP bars was explained in more detail in [8]. The results showed that bar configuration is less important than the volume fraction of fibers.…”
Section: The Concept Of Hybrid Frp Barsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for different fibers arrangement and different volume fractions of fibers are described in Table 1. The comparison between analytical considerations and numerical simulations of FRP bars was explained in more detail in [8]. The results showed that bar configuration is less important than the volume fraction of fibers.…”
Section: The Concept Of Hybrid Frp Barsmentioning
confidence: 99%
“…HFRP bars contain several types of reinforcing constituents and/or several types of adhesive constituents in a matrix. Moreover, some authors suggest that such hybridization of the constituents of FRP bars can prevent changes in their behavior, making it semi-ductile instead of linear [8,9]. Therefore, their use in the form of FRP bars as a replacement of conventional reinforcement for reinforced concrete (RC) structures has become attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Rule of Mixtures (ROM) equation, Young's modulus and other parameters were determined for the Hybrid Carbon/Basalt FRP (HC/BFRP) and for different combinations depending on carbon to basalt fiber volume fractions. Different levels of fibers substitution (carbon-to-basalt C/B) were proposed: 1:1, 1:2, 1:3, 1:4, and 1:9, which is represented in Figure 1 [36]. The Voigt model does not consider the location of the fibers; therefore, numerical analysis was made for two configurations: (i) carbon fibers in the core region and basalt fibers in the near-surface region, (ii) carbon fibers in the near-surface region and basalt fibers in the core region of the bar section.…”
Section: The Concept Of Hybrid Frp Barsmentioning
confidence: 99%
“…Numerical results indicated that the arrangement of the fibers was not of high importance for the final mechanical properties of HFRP bars with different combinations of fibers. More on the analytical and numerical investigation of Hybrid FRP bars can be found in companion papers [36,37]. Two different HFRP bars' configurations were produced by the manufacturing company.…”
Section: The Concept Of Hybrid Frp Barsmentioning
confidence: 99%
See 1 more Smart Citation